Preliminary structural characterization of human SOUL, a haem-binding protein - Freire, Filipe (2019)
The authors acknowledge financial support from Fundacao para a Ciencia e Tecnologia, Portugal through grant SFRH/BPD/30239/2006 and project PTDC/QUI/64203/2006. The authors also acknowledge the ESRF, Grenoble (beamlines ID14- EH2, ID14- EH4, ID23- EH1 and ID-29) for access and technical support during data collection.